Martin's physical pharmacy and pharmaceutical sciences - Sinko, Patrick J. (Philadelphia, Pennsylvania : Lippincott Williams & Wilkins, 2017)
Martin's Physical Pharmacy and Pharmaceutical Sciences is considered the most comprehensive text available on the physical, chemical, and biological principles that underlie pharmacology. This 7th Edition puts a stronger focus on the most essential, practical knowledge, and is updated to reflect the broadening scope and diversity of the pharmaceutical sciences
1. Interpretive tools -- 2. States of matter -- 3. Thermodynamics -
- 4. Determination of the physical properties of molecules --
5. Nonelectrolytes -- 6. Electrolyte solutions -- 7. Ionic
equilibria -- 8. Buffered and isotonic solutions --
9. Solubility and distribution phenomena -- 10. Complexation and
protein binding -- 11. Diffusion -- 12. Biopharmaceutics -- 13. Drug
release and dissolution -- 14. Chemical kinetics and stability
-- 15. Interfacial phenomena -- 16. Rheology -- 17. Colloidal
dispersions -- 18. Coarse dispersions --
19. Micromeritics -- 20. Pharmaceutical biotechnology --
21. Pharmaceutical polymers -- 22. Pharmaceutical compounding --
23. Pharmaceutical excipients -- 24. Oral solid dosage forms --
25. Drug delivery systems and drug product design
Include index
Includes bibliographical references and index
Keywords: Chemistry, Pharmaceutical; Chemistry, Physical and theoretical; Pharmaceutical chemistry